A feasibility study on SenSlope sensor networks for landslide monitoring system - Boydon, Christian John Immanuel S.; Bulatao, Ralaine Princess R.; Cervania, Vincent Margaret R.; Uy, Julieanne Patricia C.
Due to the typhoons entering the country, excessive logging activities, and the geographical setup of the country, landslides frequently occur in the Philippines causing damage to land areas and affected communities. In fact, there has been a record of 66 landslide occurrences from 2011 alone, putting the Philippines 4th in the list of countries most exposed to landslides. In February 2006, a landslide hit Southern Leyte, burying the whole village of Guinsaugon in the town of St. Bernard. Death toll for the said incident reached up to 1,126, including 246 students and 7 teachers of a local elementary school situated nearest to the slope. However, this damage to nearby communities is not just a result of these naturally-occurring landslides, but also a consequence of the absence of disaster prevention and management systems in the country. This seasonal damage of landslides to Philippine land areas can be prevented with the establishment of landslide monitoring systems. Current systems used by foreign countries, on the other hand, incur expensive costs. An effort to create an affordable nationwide landslide monitoring system was started in 2009 by students and faculty members from the University of the Philippines Diliman, creating a landslide monitoring device using inexpensive components. This product, called SenSlope (Sensor Networks for landslide monitoring system controlled by a larger government institution once the costs involved in development, production, operation, and maintenance are determined to be affordable and the whole project feasible. Product & Services SenSlope is a real-time landslide monitoring system that applies the use of sensors and wireless technology. Monitoring of a certain slope is accomplished by means of embedding 2 sets of nodes in the ground where a deep-seated landslide may occur. Data acquired by the sensors in the nodes shall be sent from the nodes to the main server via SMS. The major benefit village so lives and livelihood means may be saved from the landslide. The primary targets of the product are the municipalities which are situated near mountains and slopes. The product is suited for such locations especially in locations with high number of residents. Market Analysis The percentage of the population that may be affected by a landslide occurrence is the main indicator of the demand for Sen Slope. Sen Slope would then target specific segments to ensure maximum reach of the product's services. The company would focus on market segments with the following characteristics: 1. Sen Slope will be serving municipalities composed of determined landslide-prone barangays. Ideally, the equipment would be installed per municipality to ensure that the equipment would serve those populations in slopes that would really need monitoring. This would also entail low marketing costs since advertising will focus on local government units only rather than at a barangay level. 2. The organization would prioritize marketing and providing its services to municipalities or cities that have high population density that are running the risk of encountering landslides. Pareto Principle was applied to get the target municipalities. When Sen Slope achieves normal production of the equipment, the company may opt to offer the product to other industries abundant in the country where it may be useful, such as the mining and construction industries. SenSlope may even boast the image of those under mining and construction as safety-oriented sectors. Distribution of the product will be done directly by Sen Slope in coordination with the LGUs. Upon full implementation of the production of the equipment, it can be transported from the assembly plant and brought to the designated community through the rented vehicles. Competition The competitors of Sen Slope will be composed of similar technologies using different techniques on slope monitoring for landslides. Implementation Strategy the implementation strategy of SenSlope's business plan consists of three phases: Phase 1: Business Development and Pilot Launching This phase includes various executive, operational, marketing, research, and pilot launching actions, including company registration and incorporation, location of facilities, looking for suppliers and fabricators, seeking of grants for further product development, and product assembly and construction. Phase 2: Operational Phase This phase covers the period where the company will be in full operation. Phase 3: Expansion Phase It is planned that Sen Slope would expand its operations by building up manufacturing capacity and by including other markets and developing new products. Plans for expansion would be pursued on the sixth year of operation. Financing Requirements & Highlights Initial capital outlay requires a start-up is a feasible and profitable venture, with a payback period of 5 years. Social Profitability The most significant benefit that the LGUs will have a in using SenSlope is the improvement of the lives of the residents in the community through gaining security from landslides.